THE INFLUENCE OF PRENATAL CLASS PARTICIPATION TOWARDS MATERNAL BEHAVIOR DURING POSTNATAL IN KEDIRI DISTRICT - Dian Kumalasari; Candra Dewinataningtyas; Elin Soyanita (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2020)
Optimal puerperal care can reduce complications that occur during the puerperium. Information about childbirth care can be obtained through participation in prenatal classes. Through the prenatal class, mothers expected to gain knowledge to change the behavior of mothers regarding postnatal care. The purpose of this study was to determine the influence of participation in prenatal class on postpartum behavior. This study was a quantitative study with a descriptive-analytic study through the cross-sectional approach. The sampling technique used purposive sampling. The sample used was 80 postpartum mothers. The data analysis technique used a statistical test using Chi-square tests. The results of the study showed that mothers who attended a prenatal class by 59 (73.8%) and postpartum behavior showed an excellent category of 71 (88.8%). There were significant relationships between class participation in a prenatal class and maternal behavior during postnatal, as indicated by the value of p-value = 0.001. The activeness of mothers participating in a prenatal class can improve maternal behavior in postpartum care to be better and optimal. Keywords: prenatal classes, maternal behavior, postnatal care